Theory and Modern Applications

# A Kirchhoff-type problem involving concave-convex nonlinearities

## Abstract

A Kirchhoff-type problem with concave-convex nonlinearities is studied. By constrained variational methods on a Nehari manifold, we prove that this problem has a sign-changing solution with least energy. Moreover, we show that the energy level of this sign-changing solution is strictly larger than the double energy level of the ground state solution.

## 1 Introduction

We study the following Kirchhoff-type equation with concave-convex nonlinearities:

$$\textstyle\begin{cases} (a+\lambda \int _{\mathbb{R}^{3}} \vert \nabla u \vert ^{2}+\lambda b \int _{\mathbb{R}^{3}}u^{2} )(-\Delta u+b u) \\ \quad =Q(x) \vert u \vert ^{p-1} u+ \kappa G(x) \vert u \vert ^{q-1} u ,\quad x\in \mathbb{R}^{3}, \\ u\in H^{1}_{r}(\mathbb{R}^{3}),\end{cases}$$
(1.1)

where $$a>0$$, $$b>0$$, $$\lambda >0$$, $$\kappa <0$$, $$p\in (3,5)$$, $$q\in (0,1)$$, and $$Q,G\in C(\mathbb{R}^{3},\mathbb{R}^{+})$$ satisfying the following conditions:

$$(Q_{1})$$:

There exists $$\beta \in [0,p-2)$$ such that $$\limsup_{x\rightarrow +\infty }\frac{Q(x)}{|x|^{\beta }}<+\infty$$;

$$(G_{1})$$:

$$G(x)\in L^{2}(\mathbb{R}^{3},\mathbb{R}^{+})$$.

In recent years, the following elliptic problem has been investigated by many researchers [1, 3, 6, 9, 17, 20]:

$$\textstyle\begin{cases} - (a+b\int _{\mathbb{R}^{3}} \vert \nabla u \vert ^{2} )\Delta u=f(x,u),\quad x\in \mathbb{R}^{3}, \\ u\in H^{1}(\mathbb{R}^{3}), \end{cases}$$
(1.2)

where $$f\in C(\mathbb{R}^{3}\times \mathbb{R},\mathbb{R})$$ and $$a>0$$, $$b>0$$. The term $$\int _{\mathbb{R}^{3}}|\nabla u|^{2}$$ in (1.2) has an interesting physical application. Moreover, this problem is related to the stationary analogue of the following equation proposed by Kirchhoff :

$$u_{tt}- \biggl(a+b \int _{\Omega } \vert \nabla u \vert ^{2} \biggr) \Delta u=f(x,u).$$
(1.3)

Inspired by the variational framework given by Lions , problem (1.3) has been investigated by many researchers, and the reader is referred to [5, 7, 11, 13, 19, 22] and the references therein for more details.

Shuai  studied the ground state sign-changing solution of problem (1.2) by using Brouwer degree theory, where $$f(x,u)$$ is replaced with $$f(u)$$ with the following hypotheses:

$$(f_{1}^{\prime })$$::

$$f(s)=o(|s|)$$ as $$s\rightarrow 0$$;

$$(f_{2}^{\prime })$$::

For some constant $$p\in (4,2^{*})$$, $$\lim_{s\rightarrow \infty }\frac{f(s)}{s^{p-1}}=0$$, where $$2^{*}=+\infty$$ for $$N=1,2$$ and $$2^{*}=6$$ for $$N=3$$;

$$(f_{3}^{\prime })$$::

$$\lim_{s\rightarrow \infty }\frac{F(s)}{s^{4}}=+\infty$$, where $$F(s)=\int ^{s}_{0} f(t)\,dt$$;

$$(f_{4}^{\prime })$$::

$$\frac{f(s)}{|s|^{3}}$$ is an increasing function with respect to $$s\in \mathbb{R}\setminus \{0\}$$.

Huang and Liu  obtained the ground state sign-changing solutions of problem (1.4) with accurately two nodal domains

$$- \biggl(1+\lambda \int _{\mathbb{R}^{N}}\bigl( \vert \nabla u \vert ^{2}+V(x)u^{2}\bigr) \biggr)\bigl[\Delta u+V(x)u\bigr]= \vert u \vert ^{p-1}u, \quad x\in \mathbb{R}^{N},$$
(1.4)

where $$p\in (3,5)$$, $$\lambda >0$$ and $$V\in C(\mathbb{R}^{N},\mathbb{R})$$ is to ensure the establishment of compactness.

Deng et al.  showed the existence of radial sign-changing solutions $$u_{k}^{b}$$ of problem (1.5)

$$\textstyle\begin{cases} - (a+b\int _{\mathbb{R}^{3}} \vert \nabla u \vert ^{2} )\Delta u+V(x) u=f(x,u),\quad x\in \mathbb{R}^{3}, \\ u\in H^{1}_{r}(\mathbb{R}^{3}), \end{cases}$$
(1.5)

by constrained minimization on the Nehari manifold, where k is any positive integer. Ye  studied the existence of least energy sign-changing solutions for problem (1.5), where $$f(x,u)$$ is replaced with $$f(u)$$.

Shao and Mao  got at least one sign-changing solution of problem (1.6) with concave-convex nonlinearities

$$\textstyle\begin{cases} - (a+b\int _{\Omega } \vert \nabla u \vert ^{2} )\Delta u=\mu g(x,u)+ f(x,u),\quad \mbox{in }\Omega , \\ u=0,\quad \mbox{on }\partial \Omega , \end{cases}$$
(1.6)

by using the method of invariant sets of descending flow.

Motivated by the aforementioned works, we prove the existence of sign-changing solutions with least energy for problem (1.1) with concave-convex nonlinearities and unbounded potential by constrained variational methods on a Nehari manifold.

Now we will give the main results by Theorems 1.1 and 1.2.

### Theorem 1.1

Assume that $$(Q_{1})$$ and $$(G_{1})$$ hold, then, for $$a>0$$, $$b>0$$, $$\lambda >0$$, and $$\kappa <0$$, problem (1.1) has one least energy sign-changing solution with accurately two nodal domains.

### Theorem 1.2

Assume that $$(Q_{1})$$ and $$(G_{1})$$ hold, then, for $$a>0$$, $$b>0$$, $$\lambda >0$$, and $$\kappa <0$$, problem (1.1) has one least energy solution. Moreover $$m_{\lambda }>2c_{\lambda }$$, where $$m_{\lambda }$$ and $$c_{\lambda }$$ are defined by (2.3) and (2.5) respectively.

### Remark 1.3

Comparing with Shuai , Huang and Liu , Deng et al. , and Ye , the difference is to consider Kirchhoff-type equation with concave and convex terms, where $$Q(x)$$ is unbounded at infinity. Moreover, since $$H^{1}_{r}(\mathbb{R}^{3})\hookrightarrow L^{{q+1}}(\mathbb{R}^{3})$$ is not compact for $${q}\in (0,1)$$, this means that the appearance of concave and convex terms has greatly increased the difficulty of problem (1.1). Shao and Mao  got sign-changing solutions for Kirchhoff equation with concave and convex terms by using the method of invariant sets of descending flow. However, we want to obtain ground state sign-changing solutions of (1.1) by variational methods and constrained minimization on the sign-changing Nehari manifold. It should be addressed that our methods are different to those in .

The rest of the paper is organized as follows. In Sect. 2 we give some notations and the main lemmas related to the proof of our main results. Sections 3 and 4 give the proofs of Theorems 1.1 and 1.2, respectively.

## 2 Some notations and preliminary lemmas

Here are some notations to be used in this paper.

• C denotes a positive constant;

• $$H^{1}({\mathbb{R}}^{3})$$ denotes the usual Sobolev space with the norm $$\|u\|^{2}=\int _{\mathbb{R}^{3}}(|\nabla u|^{2}+b |u|^{2})$$;

• $$|\cdot |$$ denotes the usual norm $$L^{\bar{q}}(\mathbb{R}^{3})$$ for $$\bar{q}\in [1,\infty )$$;

• $$H^{1}_{r}({\mathbb{R}}^{3}):=\{u:u\in H^{1}({\mathbb{R}}^{3}),u(x)=u(|x|) \}$$;

• $$u^{+}:=\max \{{u,0}\}$$ and $$u^{-}:=\min \{{u,0}\}$$.

### Lemma 2.1

(see Berestycki and Lions )

Let $$N\geq 2$$ and $$u\in H_{r}^{1}({\mathbb{R}}^{N})$$, Then

$$\bigl|u(r)\bigr|\leq C_{0}\|u\|r^{\frac{1-N}{2}} \quad \textit{for } r\geq 1 ,$$

where $$C_{0}>0$$ is only related to N.

### Remark 2.2

For any $$u\in H_{r}^{1}({\mathbb{R}}^{3})$$, by $$(Q_{1})$$, $$(G_{1})$$, and Lemma 2.1, we have

$$0\leq \int _{\mathbb{R}^{3}}Q(x) \vert u \vert ^{p+1}\leq C_{1} \Vert u \Vert ^{p+1}$$

and

$$\biggl\vert \int _{\mathbb{R}^{3}}G(x) \vert u \vert ^{q+1} \biggr\vert \leq \int _{ \mathbb{R}^{3}} \bigl\vert G(x) \bigr\vert \vert u \vert ^{q+1}\leq \bigl\vert G(x) \bigr\vert _{2} \vert u \vert ^{q+1}_{2(q+1)}\leq C_{1} \Vert u \Vert ^{q+1}.$$

The energy functional $$J_{\lambda }\in C^{1}(H^{1}_{r}({\mathbb{R}}^{3}),\mathbb{R})$$ is well defined by

$$J_{\lambda }(u)=\frac{1}{2}a \Vert u \Vert ^{2} + \frac{1}{4}\lambda \Vert u \Vert ^{4}- \frac{1}{p+1} \int _{\mathbb{R}^{3}}Q(x) \vert u \vert ^{p+1}- \frac{1}{q+1}\kappa \int _{\mathbb{R}^{3}}G(x) \vert u \vert ^{q+1}.$$
(2.1)

For each $$u,v\in H^{1}_{r}({\mathbb{R}}^{3})$$,

$$\bigl\langle J^{\prime }_{\lambda }(u),v\bigr\rangle =a(u,v)+\lambda \Vert u \Vert ^{2}(u,v)- \int _{\mathbb{R}^{3}}Q(x) \vert u \vert ^{p-1}uv-\kappa \int _{\mathbb{R}^{3}}G(x) \vert u \vert ^{q-1}uv.$$
(2.2)

In order to get a sign-changing solution $$u^{\pm }\neq 0$$ of (1.1), the following functionals need to be established:

\begin{aligned}& J_{\lambda }(u)=J_{\lambda }\bigl(u^{+} \bigr)+J_{\lambda }\bigl(u^{-}\bigr)+ \frac{\lambda }{2} \bigl\Vert u^{+} \bigr\Vert ^{2} \bigl\Vert u^{-} \bigr\Vert ^{2}, \\& \bigl\langle J_{\lambda }^{\prime }(u),u^{+} \bigr\rangle =\bigl\langle J_{\lambda }^{\prime }\bigl(u^{+} \bigr),u^{+}\bigr\rangle +\lambda \bigl\Vert u^{-} \bigr\Vert ^{2} \bigl\Vert u^{+} \bigr\Vert ^{2}, \\& \bigl\langle J_{\lambda }^{\prime }(u),u^{-} \bigr\rangle =\bigl\langle J_{\lambda }^{\prime }\bigl(u^{-} \bigr),u^{-}\bigr\rangle +\lambda \bigl\Vert u^{+} \bigr\Vert ^{2} \bigl\Vert u^{-} \bigr\Vert ^{2}. \end{aligned}

Let us define

$$\mathcal{M}_{\lambda }=\bigl\{ u\in H^{1}_{r} \bigl({\mathbb{R}}^{3}\bigr):u^{\pm }\neq 0, \bigl\langle J^{\prime }_{\lambda }(u),u^{+}\bigr\rangle =\bigl\langle J^{\prime }_{ \lambda }(u),u^{-}\bigr\rangle =0\bigr\}$$

and

$$m_{\lambda }:=\inf \bigl\{ J_{\lambda }(u): u\in \mathcal{M}_{\lambda }\bigr\} .$$
(2.3)

$$\mathcal{N}_{\lambda }=\bigl\{ u\in H^{1}_{r} \bigl({\mathbb{R}}^{3}\bigr)\setminus \{0 \}:\bigl\langle J^{\prime }_{\lambda }(u),u\bigr\rangle =0\bigr\}$$
(2.4)

and

$$c_{\lambda }:=\inf \bigl\{ J_{\lambda }(u):u\in \mathcal{N}_{\lambda } \bigr\} .$$
(2.5)

### Lemma 2.3

Assume that $$(Q_{1})$$, $$(G_{1})$$, and $$u_{n}\rightharpoonup u$$ in $$H^{1}_{r}(\mathbb{R}^{3})$$ hold, then

$$\lim_{n\rightarrow \infty } \int _{\mathbb{R}^{3}}G(x) \vert u_{n} \vert ^{q+1}= \int _{\mathbb{R}^{3}}G(x) \vert u \vert ^{q+1}.$$

In particular,

$$\lim_{n\rightarrow \infty } \int _{\mathbb{R}^{3}}G(x) \bigl\vert u_{n}^{\pm } \bigr\vert ^{q+1}= \int _{\mathbb{R}^{3}}G(x) \bigl\vert u^{\pm } \bigr\vert ^{q+1}.$$

### Proof

If $$u_{n}\rightharpoonup u$$ in $$H^{1}_{r}(\mathbb{R}^{3})$$, then $$u_{n}\rightarrow u$$ in $$L^{\bar{q}}(\mathbb{R}^{3})$$ for $$\bar{q}\in (2,6)$$. According to [18, Theorem A.4, p. 134], we can obtain that $$|u_{n}|^{q+1}\rightarrow |u|^{q+1}$$ in $$L^{2}(\mathbb{R}^{3})$$. By the Hölder inequality, we have

\begin{aligned} & \biggl\vert \int _{\mathbb{R}^{3}}G(x) \vert u_{n} \vert ^{q+1}- \int _{ \mathbb{R}^{3}}G(x) \vert u \vert ^{q+1} \biggr\vert \\ &\quad \leq \int _{\mathbb{R}^{3}} \bigl\vert G(x) \bigr\vert \bigl\vert \vert u_{n} \vert ^{q+1}- \vert u \vert ^{q+1} \bigr\vert \\ &\quad \leq \bigl\vert G(x) \bigr\vert _{2} \bigl\vert |u_{n} \vert ^{q+1}- \vert u \vert ^{q+1}\bigr|_{2} \rightarrow 0. \end{aligned}

Thus, $$\lim_{n\rightarrow \infty }\int _{\mathbb{R}^{3}}G(x)|u_{n}|^{q+1}= \int _{\mathbb{R}^{3}}G(x)|u|^{q+1}$$. Similarly, $$\lim_{n\rightarrow \infty }\int _{\mathbb{R}^{3}}G(x)|u_{n}^{\pm }|^{q+1}= \int _{\mathbb{R}^{3}}G(x)|u^{\pm }|^{q+1}$$. □

### Lemma 2.4

Under the assumptions of Theorem 1.1. If $$u\in H^{1}_{r}({\mathbb{R}}^{3})$$ with $$u^{\pm }\neq 0$$, there exists a unique pair $$(s_{u},t_{u})\in (0,+\infty )\times (0,+\infty )$$ such that $$s_{u}u^{+}+t_{u}u^{-}\in \mathcal{M}_{\lambda }$$. Moreover,

$$J_{\lambda }\bigl(s_{u}u^{+}+t_{u}u^{-} \bigr)=\max_{s,t\geq 0}J_{\lambda }\bigl(su^{+}+tu^{-} \bigr).$$

### Proof

Let $$u\in H^{1}(\mathbb{R}^{3})$$ with $$u^{\pm }\neq 0$$. Define

\begin{aligned}& g_{1}(s,t)=a s^{2} \bigl\Vert u^{+} \bigr\Vert ^{2}+\lambda s^{4} \bigl\Vert u^{+} \bigr\Vert ^{4}+\lambda s^{2}t^{2} \bigl\Vert u^{+} \bigr\Vert ^{2} \bigl\Vert u^{-} \bigr\Vert ^{2} \\& \hphantom{g_{1}(s,t)={}}{}-s^{p+1} \int _{\mathbb{R}_{3}}Q(x) \bigl\vert u^{+} \bigr\vert ^{p+1}- \kappa s^{q+1} \int _{\mathbb{R}_{3}}G(x) \bigl\vert u^{+} \bigr\vert ^{q+1}, \end{aligned}
(2.6)
\begin{aligned}& g_{2}(s,t)=a t^{2} \bigl\Vert u^{-} \bigr\Vert ^{2}+\lambda t^{4} \bigl\Vert u^{-} \bigr\Vert ^{4}+\lambda s^{2}t^{2} \bigl\Vert u^{-} \bigr\Vert ^{2} \bigl\Vert u^{+} \bigr\Vert ^{2} \\& \hphantom{g_{2}(s,t)={}}{}-t^{p+1} \int _{\mathbb{R}_{3}}Q(x) \bigl\vert u^{-} \bigr\vert ^{p+1}- \kappa t^{q+1} \int _{\mathbb{R}_{3}}G(x) \bigl\vert u^{-} \bigr\vert ^{q+1}. \end{aligned}
(2.7)

According to Remark 2.2, for $$\kappa <0$$, we have $$g_{i}(s,s)>0$$ as $$s>0$$ small and $$g_{i}(t,t)<0$$ as $$t>0$$ large, where $$i=1,2$$. Then there exists $$0<\mu <\nu$$ such that

$$g_{i}(\mu ,\mu )>0,\qquad g_{i}(\nu ,\nu )< 0.$$
(2.8)

By (2.6), (2.7), (2.8), we have that

\begin{aligned}& g_{1}(\mu ,t)>0,\qquad g_{1}(\nu ,t)< 0,\quad t\in [\mu ,\nu ], \\& g_{2}(s,\mu )>0,\qquad g_{2}(s,\nu )< 0,\quad s\in [\mu ,\nu ]. \end{aligned}

From Miranda’s theorem , there exists a pair $$(s_{u},t_{u})$$ such that

$$g_{1}(s_{u},t_{u})=0,\qquad g_{2}(s_{u},t_{u})=0,\quad \mu < s_{u},t_{u}< \nu .$$

Thus, $$s_{u}u^{+}+t_{u}u^{-}\in \mathcal{M}_{\lambda }$$.

Secondly, we prove the uniqueness. Let both $$(s_{1},t_{1})$$ and $$(s_{2},t_{2})$$ satisfy $$u_{i}=s_{i}u^{+}+t_{i}u^{-}\in \mathcal{M}_{\lambda }$$ ($$i=1,2$$) and $$u_{1}=s_{1}u^{+}+t_{1}u^{-}= m s_{2}u^{+}+n t_{2}u^{-}=mu_{2}^{+}+nu^{-}_{2}$$, where $$m=\frac{s_{1}}{s_{2}}$$, $$n=\frac{t_{1}}{t_{2}}$$. By (2.6) and (2.7),

\begin{aligned}& g_{1}^{u_{1}}(1,1)=g_{1}^{u_{2}}(m,n)=g_{1}^{u_{2}}(1,1)=0, \end{aligned}
(2.9)
\begin{aligned}& g_{2}^{u_{1}}(1,1)=g_{2}^{u_{2}}(m,n)=g_{2}^{u_{2}}(1,1)=0. \end{aligned}
(2.10)

We only need to prove that $$m=n=1$$. Now, assume that $$0< m\leq n$$. By (2.9) and (2.10),

$$g_{1}^{u_{2}}(1,1)-\frac{g_{1}^{u_{2}}(m,n)}{m^{4}}=0$$
(2.11)

and

$$g_{2}^{u_{2}}(1,1)-\frac{g_{2}^{u_{2}}(m,n)}{n^{4}}=0.$$
(2.12)

If $$m<1$$, then

\begin{aligned}& \biggl(1-\frac{1}{m^{2}}\biggr)a \bigl\Vert u_{2}^{+} \bigr\Vert ^{2}+\biggl(1- \frac{n^{2}}{m^{2}}\biggr)\lambda \bigl\Vert u_{2}^{-} \bigr\Vert ^{2} \bigl\Vert u_{2}^{+} \bigr\Vert ^{2} \\& \quad =\bigl(1-m^{p-3}\bigr) \int _{\mathbb{R}^{3}}Q(x) \bigl\vert u_{2}^{+} \bigr\vert ^{p+1}+\bigl(1-m^{q-3}\bigr) \kappa \int _{\mathbb{R}^{3}}G(x) \bigl\vert u_{2}^{+} \bigr\vert ^{q+1}, \end{aligned}

this is impossible for $$\kappa <0$$. Then $$m\geq 1$$. Similarly, if $$n>1$$, (2.12) is impossible. Then $$n\leq 1$$. Thus $$m=n=1$$.

At last, let

\begin{aligned} H_{\lambda }(s,t)&=J_{\lambda } \bigl(su^{+}+tu^{-}\bigr) \\ &=\frac{a}{2}s^{2} \bigl\Vert u^{+} \bigr\Vert ^{2}+ \frac{\lambda }{4}s^{4} \bigl\Vert u^{+} \bigr\Vert ^{4}-\frac{s^{p+1}}{p+1} \int _{ \mathbb{R}^{3}}Q(x) \bigl\vert u^{+} \bigr\vert ^{p+1}-\frac{s^{q+1}}{q+1}\kappa \int _{ \mathbb{R}_{3}}G(x) \bigl\vert u^{+} \bigr\vert ^{q+1} \\ &\quad {} +\frac{a}{2}t^{2} \bigl\Vert u^{-} \bigr\Vert ^{2}+\frac{\lambda }{4}t^{4} \bigl\Vert u^{-} \bigr\Vert ^{4}- \frac{t^{p+1}}{p+1} \int _{\mathbb{R}^{3}}Q(x) \bigl\vert u^{-} \bigr\vert ^{p+1}- \frac{t^{q+1}}{q+1}\kappa \int _{\mathbb{R}_{3}}G(x) \bigl\vert u^{-} \bigr\vert ^{q+1} \\ &\quad {} +\frac{\lambda }{2}s^{2}t^{2} \bigl\Vert u^{-} \bigr\Vert ^{2} \bigl\Vert u^{+} \bigr\Vert ^{2}. \end{aligned}

Then, for $$\kappa <0$$, we have $$H_{\lambda }(s,t)>0$$ as $$|(s,t)|\rightarrow 0$$, $$H_{\lambda }(s,t)<0$$ as $$|(s,t)|\rightarrow \infty$$, and $$H_{\lambda }$$ cannot achieve the maximum point on $$\partial {\mathbb{R}^{+}}^{2}$$. Without loss of generality, we only prove that $$(0,t_{0})$$ is not a maximum point of $$H_{\lambda }$$. For $$s>0$$ small enough,

\begin{aligned} \frac{\partial H_{\lambda }}{\partial s}(s,t_{0})={}&a s \bigl\Vert u^{+} \bigr\Vert ^{2}+ \lambda s^{3} \bigl\Vert u^{+} \bigr\Vert ^{4}+\lambda st_{0}^{2} \bigl\Vert u^{-} \bigr\Vert ^{2} \bigl\Vert u^{+} \bigr\Vert ^{2} \\ &{}-s^{p} \int _{\mathbb{R}^{3}}Q(x) \bigl\vert u^{+} \bigr\vert ^{p+1}-{s^{q}}\kappa \int _{ \mathbb{R}_{3}}G(x) \bigl\vert u^{+} \bigr\vert ^{q+1}>0, \end{aligned}

this implies that $$H_{\lambda }(s,t_{0})$$ is an increasing function with respect to s, where $$s>0$$ is small enough, then $$(0,t_{0})$$ is not a maximum point of $$H_{\lambda }$$. Thus, there exists $$(s_{u},t_{u})\in {\mathbb{R}^{+}}^{2}$$ such that

$$J_{\lambda }\bigl(s_{u}u^{+}+t_{u}u^{-} \bigr)=\max_{s,t\geq 0}J_{\lambda }\bigl(su^{+}+tu^{-} \bigr).$$

□

### Lemma 2.5

Under the assumptions of Theorem 1.1. If $$\langle J^{\prime }_{\lambda }(u),u^{\pm }\rangle \leq 0$$, there exists $$(s_{u},t_{u})\in (0,1]\times (0,1]$$ such that $$s_{u}u^{+}+t_{u}u^{-}\in \mathcal{M}_{\lambda }$$ for $$u\in H^{1}_{r}({\mathbb{R}}^{3})$$ with $$u^{\pm }\neq 0$$.

### Proof

Let $$u\in H^{1}_{r}({\mathbb{R}}^{3})$$ with $$u^{\pm }\neq 0$$, by Lemma 2.4, there exists a pair $$(s_{u},t_{u})$$ such that

\begin{aligned}& s_{u}^{2}a \bigl\Vert u^{+} \bigr\Vert ^{2}+s_{u}^{4} \lambda \bigl\Vert u^{+} \bigr\Vert ^{4}+s_{u}^{2}t_{u}^{2} \lambda \bigl\Vert u^{-} \bigr\Vert ^{2} \bigl\Vert u^{+} \bigr\Vert ^{2} \\& \quad{} -s_{u}^{p+1} \int _{\mathbb{R}^{3}}Q(x) \bigl\vert u^{+} \bigr\vert ^{p+1}-s_{u}^{q+1} \kappa \int _{\mathbb{R}^{3}}G(x) \bigl\vert u^{+} \bigr\vert ^{q+1}=0. \end{aligned}
(2.13)

Since $$\langle J^{\prime }_{\lambda }(u),u^{\pm }\rangle \leq 0$$, we have that

$$a \bigl\Vert u^{+} \bigr\Vert ^{2}+ \lambda \bigl\Vert u^{+} \bigr\Vert ^{4}+\lambda \bigl\Vert u^{-} \bigr\Vert ^{2} \bigl\Vert u^{+} \bigr\Vert ^{2}- \int _{\mathbb{R}^{3}}Q(x) \bigl\vert u^{+} \bigr\vert ^{p+1}-\kappa \int _{ \mathbb{R}^{3}}G(x) \bigl\vert u^{+} \bigr\vert ^{q+1}\leq 0.$$
(2.14)

Now, assume that $$0< t_{u}\leq s_{u}$$. If $$s_{u}>1$$, by (2.13) and (2.14),

\begin{aligned}& \biggl(1-\frac{1}{s_{u}^{2}}\biggr)a \bigl\Vert u^{+} \bigr\Vert ^{2}+\biggl(1-\frac{t_{u}^{2}}{s_{u}^{2}} \biggr) \lambda \bigl\Vert u^{-} \bigr\Vert ^{2} \bigl\Vert u^{+} \bigr\Vert ^{2} \\& \quad \leq \bigl(1-s_{u}^{p-3}\bigr) \int _{ \mathbb{R}^{3}}Q(x) \bigl\vert u^{+} \bigr\vert ^{p+1}+\bigl(1-s_{u}^{q-3}\bigr)\kappa \int _{ \mathbb{R}^{3}}G(x) \bigl\vert u^{+} \bigr\vert ^{q+1}, \end{aligned}

which is contradictory for $$\kappa <0$$. Then $$s_{u}\leq 1$$. From $$0< t_{u}\leq s_{u}$$, we obtain that $$0< t_{u}\leq s_{u}\leq 1$$. □

### Lemma 2.6

Under the assumptions of Theorem 1.1, $$m_{\lambda }>0$$ can be achieved.

### Proof

For all $$u\in \mathcal{M}_{\lambda }$$, by the Sobolev embedding theorem, we have

$$a \Vert u \Vert ^{2}\leq a \Vert u \Vert ^{2}+ \lambda \Vert u \Vert ^{4}= \int _{\mathbb{R}^{3}}Q(x) \vert u \vert ^{p+1}+ \kappa \int _{\mathbb{R}^{3}}G(x) \vert u \vert ^{q+1}\leq C_{1} \Vert u \Vert ^{p+1}.$$

Then there exists $$C\geq C_{1}$$ such that $$\|u\|\geq (\frac{a}{C} )^{\frac{1}{p-1}}>0$$. Since

\begin{aligned}[b] J_{\lambda }(u)&=J_{\lambda }(u)- \frac{1}{4}\bigl\langle J_{ \lambda }^{\prime }(u),u\bigr\rangle \\ &=\frac{a}{2} \Vert u \Vert ^{2}+\frac{\lambda }{4} \Vert u \Vert ^{4}-\frac{1}{p+1} \int _{ \mathbb{R}^{3}}Q(x) \vert u \vert ^{p+1}- \frac{1}{q+1}\kappa \int _{\mathbb{R}^{3}}G(x) \vert u \vert ^{q+1} \\ & -\frac{a}{4} \Vert u \Vert ^{2}- \frac{\lambda }{4} \Vert u \Vert ^{4}+\frac{1}{4} \int _{\mathbb{R}^{3}}Q(x) \vert u \vert ^{p+1}+ \frac{1}{4}\kappa \int _{ \mathbb{R}^{3}}G(x) \vert u \vert ^{q+1} \\ &=\frac{a}{4} \Vert u \Vert ^{2}+ \biggl( \frac{1}{4}-\frac{1}{p+1} \biggr) \int _{ \mathbb{R}^{3}}Q(x) \vert u \vert ^{p+1}- \biggl( \frac{1}{q+1}-\frac{1}{4} \biggr) \kappa \int _{\mathbb{R}^{3}}G(x) \vert u \vert ^{q+1} \\ &\geq \frac{a}{8} \Vert u \Vert ^{2} \end{aligned}
(2.15)

for $$\kappa <0$$. Then

$$m_{\lambda }=\inf_{u\in {\mathcal{M}_{\lambda }}} J_{\lambda }(u)>0.$$

Let $$\{u_{n}\}\subset \mathcal{M}_{\lambda }$$ and $$J_{\lambda }(u_{n})\rightarrow m_{\lambda }$$. By Remark 2.2, we have

$$1+m_{\lambda } \geq J_{\lambda }(u_{n})- \frac{1}{p+1}\bigl\langle J_{\lambda }^{ \prime }(u_{n}),u_{n} \bigr\rangle \geq \frac{a}{8} \Vert u_{n} \Vert ^{2}.$$

This shows that $$\{u_{n}\}$$ is bounded in $$H^{1}_{r}(\mathbb{R}^{3})$$. Then there exists $$u_{\lambda }\in H^{1}_{r}(\mathbb{R}^{3})$$ such that $$u_{n}^{\pm }\rightharpoonup u_{\lambda }^{\pm }$$ in $$H^{1}_{r}(\mathbb{R}^{3})$$, $$u_{n}^{\pm }\rightarrow u_{\lambda }^{\pm }$$ in $$L^{q}(\mathbb{R}^{3})$$ for $$q\in (2,6)$$ and $$u_{n}^{\pm }(x) \rightarrow u_{\lambda }^{\pm }(x)$$ a.e. on $$\mathbb{R}^{3}$$. Since $$\{u_{n}\}\subset \mathcal{M}_{\lambda }$$, we have

$$0< C\leq a \bigl\Vert u_{n}^{\pm } \bigr\Vert ^{2}+\lambda \bigl\Vert u_{n}^{\pm } \bigr\Vert ^{4}+\lambda \bigl\Vert u_{n}^{+} \bigr\Vert ^{2} \bigl\Vert u_{n}^{-} \bigr\Vert ^{2}= \int _{\mathbb{R}^{3}}Q(x) \bigl\vert u_{n}^{\pm } \bigr\vert ^{p+1}+ \kappa \int _{\mathbb{R}^{3}}G(x) \bigl\vert u_{n}^{\pm } \bigr\vert ^{q+1}.$$

By Fatou’s lemma and Lemma 2.3,

$$a \bigl\Vert u_{\lambda }^{\pm } \bigr\Vert ^{2}+\lambda \bigl\Vert u_{\lambda }^{\pm } \bigr\Vert ^{4}+\lambda \bigl\Vert u_{ \lambda }^{+} \bigr\Vert ^{2} \bigl\Vert u_{\lambda }^{-} \bigr\Vert ^{2}\leq \int _{\mathbb{R}^{3}}Q(x) \bigl\vert u_{ \lambda }^{\pm } \bigr\vert ^{p+1}+\kappa \int _{\mathbb{R}^{3}}G(x) \bigl\vert u_{\lambda }^{\pm } \bigr\vert ^{q+1},$$

this implies that

$$\bigl\langle J^{\prime }_{\lambda }(u_{\lambda }),u_{\lambda }^{\pm } \bigr\rangle \leq 0.$$

By Lemmas 2.4 and 2.5, there exists $$(s_{{u}_{\lambda }},t_{{u}_{\lambda }})\in (0,1]\times (0,1]$$ such that $$\widetilde{u}_{\lambda }=s_{{u}_{\lambda }}u^{+}_{\lambda }+t_{{u}_{ \lambda }}u^{-}_{\lambda }\in \mathcal{M}_{\lambda }$$. Then

\begin{aligned} m_{\lambda } \leq& J_{\lambda }(\widetilde{u}_{\lambda })- \frac{1}{p+1}\bigl\langle J^{\prime }_{\lambda }( \widetilde{u}_{\lambda }), \widetilde{u}_{\lambda }\bigr\rangle \\ =& \biggl(\frac{1}{2}-\frac{1}{p+1} \biggr)a \Vert \widetilde{u}_{\lambda } \Vert ^{2}+ \biggl( \frac{1}{4}-\frac{1}{p+1} \biggr)\lambda \Vert \widetilde{u}_{\lambda } \Vert ^{4}- \biggl( \frac{1}{q+1}-\frac{1}{p+1} \biggr)\kappa \int _{\mathbb{R}^{3}}G(x) \vert \widetilde{u}_{\lambda } \vert ^{q+1} \\ \leq& \frac{p-1}{2(p+1)}a \Vert {u}_{\lambda } \Vert ^{2}+ \frac{p-3}{4(p+1)}\lambda \Vert {u}_{\lambda } \Vert ^{4}-\frac{p-q}{(q+1)(p+1)} \kappa \int _{\mathbb{R}^{3}}G(x) \vert {u}_{\lambda } \vert ^{q+1} \\ \leq& \liminf_{n} \biggl\{ \frac{p-1}{2(p+1)}a \Vert {u}_{n} \Vert ^{2}+ \frac{p-3}{4(p+1)}\lambda \Vert {u}_{n} \Vert ^{4}-\frac{p-q}{(q+1)(p+1)} \kappa \int _{\mathbb{R}^{3}}G(x) \vert {u}_{n} \vert ^{q+1} \biggr\} \\ =&\liminf_{n} \biggl(J_{\lambda }(u_{n})- \frac{1}{p+1} \bigl\langle J^{\prime }_{\lambda }({u}_{n}),{u}_{n} \bigr\rangle \biggr) \\ =&m_{\lambda }, \end{aligned}

this implies that $$s_{u_{\lambda }}=t_{u_{\lambda }}=1$$. Thus, $$\widetilde{u}_{\lambda }=u_{\lambda }$$ and $$J_{\lambda }(u_{\lambda })=m_{\lambda }$$. □

## 3 Sign-changing solutions

### Lemma 3.1

Under the assumptions of Theorem 1.1. If $$u_{\lambda }\in \mathcal{M}_{\lambda }$$ and $$J_{\lambda }(u_{\lambda })=m_{\lambda }$$, then $$J^{\prime }_{\lambda }(u_{\lambda })=0$$.

### Proof

Suppose that $$J_{\lambda }^{\prime }(u_{\lambda })\neq 0$$, then there are σ, $$\delta >0$$ such that

$$\bigl\Vert J_{\lambda }^{\prime }(u) \bigr\Vert \geq \sigma ,\quad \forall \Vert u-u_{ \lambda } \Vert \leq 3\delta .$$

Let $$D=(0.5,1.5)\times (0.5,1.5)$$. By Lemma 2.4, we obtain that

$$\iota :=\max_{(s,t)\in \partial D}J_{\lambda } \bigl(su_{\lambda }^{+}+tu_{ \lambda }^{-} \bigr)< m_{\lambda }.$$
(3.1)

For $$\varepsilon :=\min \{(m_{\lambda }-\iota )/2,\sigma \delta /8\}$$ and $$S:=B(u_{\lambda },\delta )$$, Willem [18, Lemma 2.3] produce a deformation η such that

1. (i)

$$\eta (1,u)=u$$ if $$u\notin J_{\lambda }^{-1}([m_{\lambda }-2\varepsilon ,m_{\lambda }+2 \varepsilon ])\cap S_{2\delta }$$;

2. (ii)

$$\eta (1,J_{\lambda }^{m_{\lambda }+\varepsilon }\cap S)\subset J_{ \lambda }^{m_{\lambda }-\varepsilon }$$;

3. (iii)

$$J_{\lambda }(\eta (1,u))\leq J_{\lambda }(u)$$ for all $$u\in H_{r}^{1}(\mathbb{R}^{3})$$.

At first, we show that

$$\max_{(s,t)\in \bar{D}}J_{\lambda }\bigl(\eta \bigl(1,su_{\lambda }^{+}+tu^{-}_{ \lambda } \bigr)\bigr)< m_{\lambda }.$$

For all $$(s,t)\in \bar{D}$$, by Lemma 2.4, we obtain $$J_{\lambda }(su_{\lambda }^{+}+tu_{\lambda }^{-})\leq m_{\lambda }< m_{ \lambda }+\varepsilon$$, that is, $$su_{\lambda }^{+}+tu_{\lambda }^{-}\in J_{\lambda }^{m_{\lambda }+ \varepsilon }$$. Therefore, $$J_{\lambda }(\eta (1,su_{\lambda }^{+}+tu_{\lambda }^{-}))\leq m_{ \lambda }-\varepsilon$$.

Next, we prove that

$$\eta \bigl(1,su_{\lambda }^{+}+tu_{\lambda }^{-} \bigr)\cap \mathcal{M}_{\lambda }\neq \emptyset ,\quad \forall (s,t)\in \bar{D}.$$

Define $$h(s,t)=\eta (1,su_{\lambda }^{+}+tu_{\lambda }^{-})$$ and $$\psi :[0,1]\times \bar{D}\rightarrow \mathbb{R}^{2}$$, for any $$\vartheta \in [0,1]$$, we have

\begin{aligned} \psi \bigl(\vartheta ,(s,t)\bigr) =&\bigl(\bigl\langle J_{\lambda }^{\prime } \bigl(\eta \bigl(\vartheta ,su_{ \lambda }^{+}+tu_{\lambda }^{-} \bigr)\bigr),\bigl(\eta \bigl(\vartheta ,su_{\lambda }^{+}+tu_{ \lambda }^{-} \bigr)\bigr)^{+}\bigr\rangle , \\ &\bigl\langle J_{\lambda }^{\prime } \bigl(\eta \bigl( \vartheta ,su_{\lambda }^{+}+tu_{\lambda }^{-} \bigr)\bigr),\bigl(\eta \bigl(\vartheta ,su_{ \lambda }^{+}+tu_{\lambda }^{-} \bigr)\bigr)^{-}\bigr\rangle \bigr). \end{aligned}

Let

\begin{aligned}& \psi _{0}=\psi _{0}(1,\cdot )=\bigl\langle J_{\lambda }^{\prime }\bigl(su_{\lambda }^{+}+tu_{ \lambda }^{-} \bigr)su_{\lambda }^{+},J_{\lambda }^{\prime } \bigl(su_{\lambda }^{+}+tu_{ \lambda }^{-} \bigr)tu_{\lambda }^{-}\bigr\rangle , \\& \psi _{1}=\psi _{1}(1,\cdot )=\bigl\langle J_{\lambda }^{\prime }\bigl(h(s,t)\bigr)h^{+}(s,t),J_{ \lambda }^{\prime } \bigl(h(s,t)\bigr)h^{-}(s,t)\bigr\rangle . \end{aligned}

By a simple calculation, $$\operatorname{deg}(\psi _{0},D,0)=1$$. According to (3.1), we obtain that $$u_{\lambda }=h$$ on ∂D and from homotopy invariance that

$$\deg (\psi _{1},D,0)=\deg (\psi _{0},D,0)=1.$$

Then there exists a pair $$(s_{0},t_{0})\in D$$ such that $$\psi _{1}(s_{0},t_{0})=0$$ and $$\eta (1,s_{0}u_{\lambda }^{+}+t_{0}u^{-}_{\lambda })=h(s_{0},t_{0}) \in \mathcal{M}_{\lambda }$$, which contradicts (3.1). Therefore, $$u_{\lambda }$$ is a critical point of $$J_{\lambda }$$, and so a sign-changing solution of (1.1). □

### Proof of Theorem 1.1

Firstly, by the preceding lemmas, there exists $$u_{\lambda }\in \mathcal{M}_{\lambda }$$ such that $$J_{\lambda }(u_{\lambda })=m_{\lambda }$$ and $$J_{\lambda }^{\prime }(u_{\lambda })=0$$. Thus, problem (1.1) has one least energy sign-changing solution $$u_{\lambda }$$.

Secondly, we prove that $$u_{\lambda }$$ has only two nodal domains. Assume that $$u_{\lambda }=u_{1}+u_{2}+u_{3}$$ with

\begin{aligned}& u_{i} \not \equiv 0, \qquad u_{1}\geq 0, \qquad u_{2}\leq 0, \\& \operatorname{supp} (u_{i})\cap \operatorname{supp} (u_{j})=\emptyset , \quad i\neq j , i,j=1,2,3 . \end{aligned}

Setting $$w=u_{1}+u_{2}$$ with $$w^{+}=u_{1}$$ and $$w^{-}=u_{2}$$, i.e., $$w^{\pm }\neq 0$$. Since $$J_{\lambda }^{\prime }(u_{\lambda })=0$$, we get

\begin{aligned}& \bigl\langle J_{\lambda }^{\prime }(w),w^{+}\bigr\rangle =\bigl\langle J_{\lambda }^{ \prime }(u_{1}+u_{2}),u_{1} \bigr\rangle \leq \bigl\langle J_{\lambda }^{\prime }(u_{\lambda }),u_{1} \bigr\rangle =0, \\& \bigl\langle J_{\lambda }^{\prime }(w),w^{-}\bigr\rangle =\bigl\langle J_{\lambda }^{ \prime }(u_{1}+u_{2}),u_{2} \bigr\rangle \leq \bigl\langle J_{\lambda }^{\prime }(u_{\lambda }),u_{2} \bigr\rangle =0. \end{aligned}

By Lemma 2.5, there exists $$(s_{w},t_{w})\in (0,1]\times (0,1]$$ such that

$$s_{w}w^{+}+t_{w}w^{-}=s_{w}u_{1}+t_{w}u_{2} \in \mathcal{M}_{\lambda },\quad m_{\lambda }\leq J_{\lambda }(s_{w}u_{1}+t_{w}u_{2}).$$

Note that $$\langle J_{\lambda }^{\prime }(u_{\lambda }),u_{\lambda }\rangle =0$$ and $$\langle J_{\lambda }^{\prime }(s_{w}u_{1}+t_{w}u_{2}),s_{w}u_{1}+t_{w}u_{2} \rangle =0$$, we have

\begin{aligned} m_{\lambda } =&J_{\lambda }(u_{\lambda })- \frac{1}{p+1} \bigl\langle J_{\lambda }^{\prime }(u_{\lambda }),u_{\lambda } \bigr\rangle \\ =& \biggl(\frac{1}{2}-\frac{1}{p+1} \biggr)a \Vert u_{\lambda } \Vert ^{2}+ \biggl(\frac{1}{4}- \frac{1}{p+1} \biggr)\lambda \bigl( \Vert u_{\lambda } \Vert ^{2}\bigr)^{2} \\ &{}- \biggl(\frac{1}{q+1}- \frac{1}{p+1} \biggr)\kappa \int _{\mathbb{R}^{3}}G(x) \vert u_{\lambda } \vert ^{q+1} \\ >& \biggl(\frac{1}{2}-\frac{1}{p+1} \biggr)a \bigl( \Vert u_{1} \Vert ^{2}+ \Vert u_{2} \Vert ^{2} \bigr) \\ &{}+ \biggl(\frac{1}{4}-\frac{1}{p+1} \biggr) \lambda \bigl( \Vert u_{1} \Vert ^{4}+2 \Vert u_{1} \Vert ^{2} \Vert u_{2} \Vert ^{2}+ \Vert u_{2} \Vert ^{4} \bigr) \\ &{} - \biggl(\frac{1}{q+1}-\frac{1}{p+1} \biggr)\kappa \int _{\mathbb{R}^{3}}G(x) \bigl( \vert u_{1} \vert ^{q+1}+ \vert u_{2} \vert ^{q+1} \bigr) \\ \geq &\biggl(\frac{1}{2}-\frac{1}{p+1} \biggr)a \bigl( \Vert s_{w}u_{1} \Vert ^{2}+ \Vert t_{w}u_{2} \Vert ^{2} \bigr) \\ &{}+ \biggl( \frac{1}{4}-\frac{1}{p+1} \biggr)\lambda \bigl( \Vert s_{w}u_{1} \Vert ^{4}+2 \Vert s_{w}u_{1} \Vert ^{2} \Vert t_{w}u_{2} \Vert ^{2}+ \Vert t_{w}u_{2} \Vert ^{4} \bigr) \\ &{}- \biggl(\frac{1}{q+1}-\frac{1}{p+1} \biggr)\kappa \int _{\mathbb{R}^{3}}G(x) \bigl( \vert s_{w}u_{1} \vert ^{q+1}+ \vert t_{w}u_{2} \vert ^{q+1} \bigr) \\ =& \biggl(\frac{1}{2}-\frac{1}{p+1} \biggr)a \Vert s_{w}u_{1}+t_{w}u_{2} \Vert ^{2}+ \biggl(\frac{1}{4}-\frac{1}{p+1} \biggr) \lambda \bigl( \Vert s_{w}u_{1}+t_{w}u_{2} \Vert ^{2} \bigr)^{2} \\ &{} - \biggl(\frac{1}{q+1}-\frac{1}{p+1} \biggr)\kappa \int _{\mathbb{R}^{3}}G(x) \vert s_{w}u_{1}+t_{w}u_{2} \vert ^{q+1} \\ =&J_{\lambda }(s_{w}u_{1}+t_{w}u_{2})- \frac{1}{p+1}\bigl\langle J_{ \lambda }^{\prime }(s_{w}u_{1}+t_{w}u_{2}),s_{w}u_{1}+t_{w}u_{2} \bigr\rangle \\ =&J_{\lambda }(s_{w}u_{1}+t_{w}u_{2}) \\ \geq& m_{\lambda }, \end{aligned}

## 4 Ground state solutions

### Lemma 4.1

(Mountain pass theorem )

Let X be a Banach space, $$I \in C^{1}(X, \mathbb{R})$$, $$e \in X$$, and $$\rho > 0$$ such that $$\|e\|> \rho$$ and

$$\inf_{\|u\|=\rho } I(u) > I(0) \geq I(e).$$

If I satisfies the $$(PS)_{c}$$ condition with

\begin{aligned}& c := \inf_{\gamma \in \Gamma }\max_{t\in [0,1]}I\bigl(\gamma (t)\bigr), \\& \Gamma := \bigl\{ \gamma \in C\bigl([0, 1], X\bigr) : \gamma (0) = 0, \gamma (1) = e \bigr\} , \end{aligned}

then c is a critical value of I.

### Lemma 4.2

Under the assumptions of Theorem 1.2, there exist $$e\in H^{1}_{r}(\mathbb{R}^{3})$$ and $$\rho > 0$$ such that $$\|e\|>\rho$$ and $$\inf_{\|u\|=\rho }J_{\lambda }(u)>J_{\lambda }(0)> J_{\lambda }(e)$$.

### Proof

For all $$u\in H^{1}_{r}(\mathbb{R}^{3})$$, by Remark 2.2,

\begin{aligned} J_{\lambda }(u)&=\frac{a}{2} \Vert u \Vert ^{2}+\frac{\lambda }{4} \Vert u \Vert ^{4}- \frac{1}{p+1} \int _{\mathbb{R}^{3}}Q(x) \vert u \vert ^{p+1}- \frac{\kappa }{q+1} \int _{\mathbb{R}^{3}}G(x) \vert u \vert ^{q+1} \\ &\geq \frac{a}{2} \Vert u \Vert ^{2}+ \frac{\lambda }{4} \Vert u \Vert ^{4}- \frac{C_{1}}{p+1} \Vert u \Vert ^{p}, \end{aligned}

then there exists $$\rho >0$$ such that

$$b:=\inf_{\|u\|=\rho }J_{\lambda }(u)>0=J_{\lambda }(0).$$

Let $$t\geq 0$$, we have

$$J_{\lambda }(tu)=\frac{t^{2}}{2}a \Vert u \Vert ^{2}+\frac{t^{4}}{4}\lambda \Vert u \Vert ^{4}- \frac{t^{p+1}}{p+1} \int _{\mathbb{R}^{3}}Q(x) \vert u \vert ^{p+1}- \frac{t^{q+1}}{q+1}\kappa \int _{\mathbb{R}^{3}}G(x) \vert u \vert ^{q+1},$$

then there exists $$e:=tu$$ such that $$\|e\|>\rho$$ and $$J_{\lambda }(e)<0$$. □

### Lemma 4.3

Under the assumptions of Theorem 1.2. $$J_{\lambda }$$ satisfies the $$(P S)_{c}$$ condition.

### Proof

Let $$\{u_{n}\}\subset H_{r}^{1}(\mathbb{R}^{3})$$ and $$J_{\lambda }(u_{n})\rightarrow c$$, $$J_{\lambda }(u_{n})\rightarrow 0$$ as $$n\rightarrow \infty$$. By (2.15) in Lemma 2.6 above, it is easy to see that $$\{u_{n}\}$$ is bounded in $$H_{r}^{1}(\mathbb{R}^{3})$$. Going if necessary to a subsequence, $$u_{n}\rightharpoonup u$$ in $$H^{1}_{r}(\mathbb{R}^{3})$$, $$u_{n}\rightarrow u$$ in $$L^{s}(\mathbb{R}^{3})$$ for $$s\in (2,6)$$, and $$u_{n}(x)\rightarrow u(x)$$ a.e. on $$\mathbb{R}^{3}$$, then by $$(G_{1})$$ we have

\begin{aligned}& \biggl\vert \int _{\mathbb{R}^{3}}G(x) \vert u_{n} \vert ^{q}(u_{n}-u) \biggr\vert \\& \quad \leq \int _{\mathbb{R}^{3}} \bigl\vert G(x) \bigr\vert \bigl| \vert u_{n} \vert ^{q}|u_{n}-u \vert \bigr\vert \\& \quad \leq \biggl( \int _{\mathbb{R}^{3}} \bigl\vert G(x) \bigr\vert ^{2} \biggr)^{ \frac{1}{2}} \biggl( \int _{\mathbb{R}^{3}} \vert u_{n} \vert ^{2q} \vert u_{n}-u \vert ^{2} \biggr)^{\frac{1}{2}} \\& \quad \leq \bigl\vert G(x) \bigr\vert _{2} \biggl( \int _{\mathbb{R}^{3}} \vert u_{n} \vert ^{2q+2} \biggr)^{\frac{q}{2q+2}} \biggl( \int _{\mathbb{R}^{3}} \vert u_{n}-u \vert ^{2q+2} \biggr)^{\frac{1}{2q+2}} \\& \quad \leq C \bigl\vert G(x) \bigr\vert _{2} \Vert u_{n} \Vert ^{q} \vert u_{n}-u \vert _{2q+2}\rightarrow 0. \end{aligned}

Since

\begin{aligned}& \bigl\langle J^{\prime }_{\lambda }(u_{n})-J^{\prime }_{\lambda }(u),u_{n}-u \bigr\rangle \rightarrow 0, \\& \int _{\mathbb{R}^{3}}Q(x) \bigl(\vert u_{n} \vert ^{p}-\vert u \vert ^{p}\bigr)(u_{n}-u)\rightarrow 0 \end{aligned}

and

\begin{aligned} &\bigl(a+\lambda \Vert u_{n} \Vert ^{2}\bigr) \Vert u_{n}-u \Vert ^{2} \\ &\quad = \bigl\langle J^{\prime }_{\lambda }(u_{n})-J^{\prime }_{\lambda }(u),u_{n}-u \bigr\rangle +\lambda \bigl( \Vert u \Vert ^{2}- \Vert u_{n} \Vert ^{2} \bigr) \langle u,u_{n}-u \rangle \\ &\quad\quad {}+ \int _{\mathbb{R}^{3}}Q(x) \bigl(\vert u_{n} \vert ^{p}-\vert u \vert ^{p}\bigr)(u_{n}-u)+ \int _{\mathbb{R}^{3}}G(x) \bigl(\vert u_{n} \vert ^{p}-\vert u \vert ^{p}\bigr)(u_{n}-u). \end{aligned}

Thus, $$u_{n}\rightarrow u$$ in $$H^{1}_{r}(\mathbb{R}^{3})$$. □

Set

$$c_{1}=\inf_{u\in H_{r}^{1}(\mathbb{R}^{3})\setminus \{0\}}\max_{t \geq 0}J_{\lambda }(tu).$$

### Lemma 4.4

Under the assumptions of Theorem 1.2, we have $${c}=c_{\lambda }=c_{1}$$.

### Proof

Similar to the proof of Lemma 2.4, for all $$u\in H_{r}^{1}(\mathbb{R}^{3})\setminus \{0\}$$, there exists unique $$t_{u}u\in \mathcal{N}$$ such that $$J_{\lambda }(t_{u}u)=\max_{t\geq 0}J_{\lambda }(tu)$$, this implies that $$c_{\lambda }\leq c_{1}$$.

For each $$\gamma \in \Gamma$$, it follows from the property of $$\mathcal{N}$$ that $$\gamma (t)$$ crosses $$\mathcal{N}$$ as t varying over $$[0,1]$$. Since $$\gamma (0)=0$$, $$J_{\lambda }(\gamma (1))<0$$, then

$$\max_{t\in [0,1]}J_{\lambda } \bigl(\gamma (t)\bigr)\geq \inf_{u\in \mathcal{N}}J_{\lambda }(u)=c_{\lambda }.$$

Therefore $$c\geq c_{\lambda }$$. On the other hand, for $$u\in H_{r}^{1}(\mathbb{R}^{3})\setminus \{0\}$$, we have that $$J_{\lambda }(tu)<0$$ for t large enough, and then

$$\max_{t\geq 0}J_{\lambda }(tu) \geq \max_{t\in [0,1]}J_{\lambda }(tu) \geq \inf _{\gamma \in \Gamma }\max_{t\in [0,1]}J_{\lambda }\bigl( \gamma (t)\bigr)=c.$$

Therefore $$c_{1}\geq c$$. □

### Proof of Theorem 1.2

According to Lemmas 4.1, 4.2, 4.3, and 4.4, we obtain that problem (1.1) has one least energy solution.

Now we prove $$m_{\lambda }>2c_{\lambda }$$. By the proof of Theorem 1.1, there exists $$u_{\lambda }\in \mathcal{M}_{\lambda }$$ such that $$J_{\lambda }(u_{\lambda })=m_{\lambda }$$. By Lemmas 2.4 and 4.4, we have

\begin{aligned} m_{\lambda }&=J_{\lambda }(u_{\lambda }) \\ &\geq J_{\lambda }\bigl(su_{\lambda }^{+}+tu_{\lambda }^{-} \bigr) \\ &= J_{\lambda }\bigl(su_{\lambda }^{+} \bigr)+J_{\lambda }\bigl(tu_{\lambda }^{-}\bigr)+ \frac{s^{2}t^{2}}{2}\lambda \bigl\Vert u_{\lambda }^{+} \bigr\Vert ^{2} \bigl\Vert u_{\lambda }^{-} \bigr\Vert ^{2} \\ &> J_{\lambda }\bigl(su_{\lambda }^{+} \bigr)+J_{\lambda }\bigl(tu_{\lambda }^{-}\bigr) \\ &\geq 2c_{\lambda }. \end{aligned}

□

## Availability of data and materials

Data sharing not applicable to this article as no datasets were generated or analysed during the current study.

## References

1. Alves, C.O., Corrêa, F.J.S.A., Ma, T.F.: Positive solutions for a quasilinear elliptic equation of Kirchhoff type. Comput. Math. Appl. 49, 85–93 (2005)

2. Berestycki, H., Lions, P.L.: Nonlinear scalar field equations. I. Existence of a ground state. Arch. Ration. Mech. Anal. 82(4), 313–345 (1983)

3. Cheng, B.T., Wu, X.: Existence results of positive solutions of Kirchhoff problems. Nonlinear Anal. 71, 4883–4892 (2009)

4. Deng, Y.B., Peng, S.J., Shuai, W.: Existence and asymptotic behavior of nodal solutions for the Kirchhoff-type problems in $$\mathbb{R}^{3}$$. J. Funct. Anal. 269, 3500–3527 (2015)

5. Duan, Y.L., Zhou, Y.G.: Existence of solutions for Kirchhoff-type equations with unbounded potential. Electron. J. Differ. Equ. 2017, 184 (2017)

6. He, H.M., Zou, W.M.: Existence and concentration behavior of positive solutions for a Kirchhoff equation in $$\mathbb{R}^{3}$$. J. Differ. Equ. 2, 1813–1834 (2012)

7. He, Y., Li, G.B., Peng, S.J.: Concentrating bound states for Kirchhoff-type problems in $$\mathbb{R}^{3}$$ involving critical Sobolev exponents. Adv. Nonlinear Stud. 14(2), 483–510 (2014)

8. Huang, Y.S., Liu, Z.: On a class of Kirchhoff type problems. Arch. Math. 102, 127–139 (2014)

9. Jeanjean, L.: On the existence of bounded Palais–Smale sequences and application to a Landsman–Lazer-type problem set on $$\mathbb{R}^{N}$$. Proc. R. Soc. Edinb., Sect. A 129(2), 787–809 (1999)

10. Kirchhoff, G.: Mechanik. Teubner, Leipzig (1883)

11. Liang, S.H., Zhang, J.H.: Existence of solutions for Kirchhoff-type problems with critical nonlinearity in $$\mathbb{R}^{3}$$. Nonlinear Anal., Real World Appl. 17, 126–136 (2014)

12. Lions, J.L.: On some questions in boundary value problems of mathematical physics. In: Contemporary Developments in Continuum Mechanics and Partial Differential Equations, Proc. Internat. Sympos., Inst. Mat., Univ. Fed. Rio de Janeiro, 1977. North-Holland Math. Stud., vol. 30, pp. 284–346. North-Holland, Amsterdam (1978)

13. Mao, A.M., Luan, S.X.: Sign-changing solutions of a class of nonlocal quasilinear elliptic boundary value problems. J. Math. Anal. Appl. 383(1), 239–243 (2011)

14. Miranda, C.: Un’osservazione su un teorema di Brouwer. Boll. Unione Mat. Ital. 3(2), 5–7 (1940)

15. Shao, M.Q., Mao, A.M.: Signed and sign-changing solutions of Kirchhoff type problems. J. Fixed Point Theory Appl. 20(1), 2 (2018)

16. Shuai, W.: Sign-changing solutions for a class of Kirchhoff-type problem in bounded domains. J. Differ. Equ. 259(4), 1256–1274 (2015)

17. Sun, J.T., Tang, C.L.: Existence and multiplicity of solutions for Kirchhoff type equations. Nonlinear Anal. 74, 1212–1222 (2011)

18. Willem, M.: Minimax Theorems. Birkhäuser, Boston (1996)

19. Wu, X.: Existence of nontrivial solutions and high energy solutions for Schrödinger–Kirchhoff-type equations in $$\mathbb{R}^{3}$$. Nonlinear Anal., Real World Appl. 12, 1278–1287 (2011)

20. Xie, Q.L., Wu, X.P., Tang, C.L.: Existence and multiplicity of solutions for Kirchhoff type problems with critical exponent. Commun. Pure Appl. Anal. 12(6), 2773–2786 (2013)

21. Ye, H.Y.: The existence of least energy nodal solutions for some class of Kirchhoff equations and Choquard equations in $$\mathbb{R}^{N}$$. J. Math. Anal. Appl. 431(2), 935–954 (2015)

22. Zhang, Z.T., Perera, K.: Sign-changing solutions of Kirchhoff-type problems via invariant sets of descent flow. J. Math. Anal. Appl. 317(2), 456–463 (2006)

## Acknowledgements

The authors would like to thank the referees for their useful suggestions which have significantly improved the paper.

## Funding

This work was supported financially by the National Natural Science Foundation of China (11871302).

## Author information

Authors

### Contributions

All authors contributed equally and significantly in writing this article. All authors read and approved the final manuscript.

### Corresponding author

Correspondence to Lishan Liu.

## Ethics declarations

Not applicable.

### Competing interests

The authors declare that they have no competing interests.

Not applicable.

## Rights and permissions 